The accuracy of pain drawing in identifying psychological distress in low back pain—systematic review and meta-analysis of diagnostic studies - Bertozzi, Lucia (J Phys Ther Sci, 2015)
The aim of this systematic review and meta-analysis was to estimate the accuracy of qualitative pain drawings (PDs) in identifying psychological distress in subacute and chronic low back pain (LBP) patients. [Subjects and Methods] Data were obtained from searches of PubMed, EBSCO, Scopus, PsycINFO and ISI Web of Science from their inception to July 2014. Quality assessments of bias and applicability were conducted using the Quality of Diagnostic Accuracy Studies-2 (QUADAS-2). [Results] The summary estimates were: sensitivity=0.45 (95% CI 0.34, 0.61), specificity=0.66 (95% CI 0.53, 0.82), positive likelihood ratio=1.23 (95% CI 0.93, 1.62), negative likelihood ratio=0.84 (95% CI 0.70, 1.01), and diagnostic odds ratio=1.46 (95% CI 0.79, 2.68). The area under the curve was 78% (CI, 57 to 99%). [Conclusion] The results of this systematic review do not show broad and unqualified support for the accuracy of PDs in detecting psychological distress in subacute and chronic LBP.